Determining Factors Influencing The E-Waste Separation Intention Among Mobile Phone Repairers In Bangladesh - Rahman, Ashikur (2023)
There is an enormous growth in mobile phone consumption worldwide which leads to generation of a large volume of e-waste every year. In Bangladesh, mobile phones are constantly repaired by replacing old batteries, screens, and accessories, which ultimately causes massive e-waste generation. Insufficient knowledge of e-waste separation causes individuals to dispose of e-waste with other waste, which cannot be used in the recycling process. To study the intention of e-waste separation, it is essential to disclose the influencing factors. Therefore, current study integrates the value belief norm (VBN) model, self-determination theory (SDT) and institutional theory (IT) to predict mobile phone repairers’ e-waste separation intention. Survey research design was employed whereas data includes valid 200 respondents (repairers), collected through survey questionnaire (printed), by employing purposive sampling. PLS-SEM was applied on the collected data for hypotheses testing. The integrated model explained 73.5% of the variance of e-waste separation intention. This result indicates the importance of integrating models to enhance its explanatory power in predicting behavioural intention. The finding of this study indicates that, altruistic values, openness to change values, environmental beliefs, personal norms, amotivation, external regulation, introjected regulation, identified regulation,